Mus musculusفي الفئران البيض (coker 310) تاثير اطعام بذور القطن صنف - الشمري, علي عبيس عبد (Al-Nahrain Journal of Science, 2018)
The effect of feeding with cottonseed(Coker 310) which is cultivated in Iraq onsome parameters on white mice Mus musculuswas studied. The parameters were grosscharacters such as body weight, and someanatomical parameters; weight of liver, kidneyand spleen. In addition the effect on male germcells was studied by measuring the sperm headabnormalities, some cytogenetic parameterswere studied as well, among these, theinduction of micronuclei (Mn) and mitoticindex (MI) in femur bone marrow.Results showed that there was nonsignificantdifferences in body weight betweencontrol group and treated group after ten daysof feeding with cottonseeds. Similar resultswere obtained for weights of liver and kidney.The average weight was 1.47g for controlgroup and 1.25g for treated group, kidneyweights were 0.44g (control) and 0.395g forcottonseed group. On the other hand, spleenweights were affected significantly (P≤0.05) asthe weight of control groups was 0.104g andthe treated group was 0.066, ie., there was36.5% reduction.The effect on male germ cells wasstatistically significant (P≤0.05), since thetreatment (ie, feeding with cottonseed)increased the level of abnormal sperms to5.5/1000 sperm compared to control group(1.65/1000 sperm).Cytogenetic parameters were significantlyaffected (P≤0.05) as the Mn raised to 6.07/1000 cells compared to background level3.2/1000 cells (control group), while the MIreduced in treated group to 3.22 compared to7.18 of the control group